Contextual-Based Teaching Materials: Solid Bioethanol Producing from Rice-Washing Wastewater - Indriani Agustin; Sjaeful Anwar; Qonita Mu'minah (Jambura Journal of Educational Chemistry, 2026)
Providing contextual chemistry teaching materials remains a challenge, given that currently available textbooks still do little to connect the material to real life. This study aims to develop instructional materials on alcohol compounds in the context of producing solid bioethanol from rice-washing wastewater using the 4STMD method. The research method used was Developmental Research (DR), which consists of three stages: design, development, and evaluation. The participants involved in this study were 67 twelfth grade high school students in Bandung for the characterization test and 62 students for the comprehension test, as well as a feasibility test involving 5 high school chemistry teachers. The development process began with the design stage, which produced a preliminary draft of the instructional materials. Next, during the development stage the 4STMD instructional material development method was used, a selection process was conducted, resulting in 2 Learning Objectives and 12 Concept Labels based on 8 textbooks. From this stage, the characterization process identified 6 texts categorized as difficult, which were then subjected to didactic reduction through the use of explanations in the form of images and symbols, sentence reformulation, and omission. In the evaluation stage, the results of the instructional material feasibility test showed a “highly feasible” rating of 89.76%, and the results of the student comprehension test indicated that the instructional material had a high level of comprehension at 90.9%, placing it in the “self-directed learning material” category.